L’économie territoriale de l’enrichissement (ETE) dans les territoires de montagne - Delphine Rime (Revue de Géographie Alpine)
This article looks at the development of mountain areas in terms of the economy of enrichment (Boltanski & Esquerre, 2017). According to this theory, capitalism today is developing through the creation of value from the past, from heritage and more generally from culture. This economy therefore differs from the industrial economy, which pursues novelty (modernity). From a territorial point of view, by contrast with the industrial economy, sectoral competitiveness is not an imperative in the TEE: development through the territorial economy of enrichment (TEE) depends on relations between a variety of activities and actors without these necessarily achieving a particular critical mass. Peripheral regions are therefore able to benefit from the TEE, whereas they generally experience difficulty in developing through the industrial economy. For mountain areas, the article examines two “ideal-type” situations arising from 20th-century pathways: areas that depend mainly on agriculture, crafts and mature industries (not specialising in a particular industrial branch), and areas that have specialised in the tourist industry.